ROKOK, ALKOHOL DAN CINTA: TIGA PERBINCANGAN MENUJU “SURGA” (PEMAKNAAN AUDIENS FILM CONSTANTINE DALAM RANAH FIKSI PENGGEMAR) - Yongky Gigih Prasisko (POETIKA, 2013)
AbstractThe transition of traditional media toward new media provide the change of media communications systemtoward the audience; which is originally transmitive, narrowcast and centralized become dialectical, broadcast andscattered. New media provides a space for the audience to interpret media content, with its dialectic system, the meaningbecome plural and heterogeneous. Audiences are no longer a passive object but subjects who actively participated in themedia. The concept of an active audience get the material in the form of fan fiction on fanfiction.net site, in this contextConstantine movie audience, make a fictional story with characters and settings are still using film as a new form ofinterpretation and meaning of the film. In the realm of fanfiction, has created dialectic between the audiences with themedia, through which new meanings will continue to emerge from the diverse audience interpretation.Keywords: Audience, fanfiction, Constantine, ecstasy, investment